Evaluating the knowledge of pain management and the impact of PASHA (Pain Assessment Stimulation and Healing Application) on pain intensity among Indonesian adolescents - Imelda Rahmayunia Kartika; Fitrianola Rezkiki; Hafiz Nugraha (Belitung Raya Foundation, 2024)
Background: Effective pain management for adolescents is essential because it significantly affects their quality of life and can prevent the development of chronic pain. Although there have been advancements in this field, managing pain effectively remains challenging, highlighting the need for innovative approaches that combine technology with clinical practice. Objective: This study aimed to assess adolescents' pain management knowledge and evaluate the effectiveness of the PASHA (Pain Assessment Stimulation and Healing Application) in reducing pain intensity among adolescents. Methods: A combination of a cross-sectional design (N = 461) and one group pretest-posttest approach (N = 60) were employed in a Junior High School at Bukittinggi, West Sumatera, Indonesia. Data were collected from June to August 2022 using the Nursing Outcomes Classification (NOC) to assess pain management knowledge and the Numeric Rating Scale (NRS) to measure pain intensity. The intervention involved using the PASHA application for three days, with pain intensity assessed before and after. Descriptive statistics and Paired t-test were used for data analysis. Results: Headaches were the most prevalent pain type among adolescents (60.5%). Many adolescents lacked adequate knowledge about pain management (57.7%) and self-medication practices (49.2%). Massage/acupressure therapy was the most recognized pain management strategy (39.1%), while aromatherapy was the least known (4.8%). The PASHA application significantly reduced pain intensity (Mean difference = 0.567, p <0.001). Conclusion: Adolescents had moderate knowledge gaps in pain management, particularly in chronic pain and non-pharmacological strategies. The PASHA application effectively reduced pain intensity, suggesting its potential to enhance pain management outcomes. Future research is necessary to validate the findings.